Soil amelioration potential of young plantations of black wattle (Acacia mollissima De Willd.) - Gupta, S.K.; Bhardwaj, S.D. (Indian Journal of Agroforestry, 2020)
High density, pure plantations of Black Wattle (Acacia mollissima De Willd.), an exotic were raised at different sites in the mid hills of Himachal Pradesh at anÂ  elevational range of 900-1200 meters embodied in the transitional zone. Physico-chemical properties of soil at different depths (0-50 cm) from adjoining area having no plantation and from the selected study sites were analyzed so as to determine the influence of plantations on site enrichment. Analysis of results have indicated that plantations of Acacia mollissima marked a considerable reduction in soil pH, improvement inÂ  organic carbon status, available nitrogen, phosphorous and potassium in comparison to control at all the depth sand sites studied. Availability of these nutrients was reduced in sub-surface layers. Since a large chunk of these nutrients removed from soil were bound in the components of above ground biomass and retention of only leaves with twigs at site after harvesting would surely compensate the depletion to some extent.